Penerapan Model Pembelajaran Kooperatif Tipe Kancing Gemerincing Untuk Meningkatkan Penguasaan Materi Perubahan Sosial Siswa - Warsun Warsun (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2021)
In the Kancing Gemerincing activity, each group member gets the opportunity to make their contribution and listen to the views and thoughts of other members. The objectives of this study are: 1) To determine the mastery of the Sociology teaching materials of students, 2) To determine the improvement of student learning achievement, 3) To determine the increase in student activity. Data collected through observation, field notes, and interviews. Data were analyzed descriptively qualitatively. The flow model of the validity of the data was checked by investigator triangulation. From these findings, the researchers concluded that learning with the Kancing Gemerincing model, in general, can improve student achievement and student activities.